Heating of refractory cathodes by high-pressure arc plasmas: I - Benilov, M. S. (2022)
A model of the near-cathode plasma layer in a plasma under a pressure of the order of one or several bars is reconsidered on the basis of recent theoretical results. Physics of the near-cathode layer is analysed in the range of near-cathode voltage drops of up to 50 V, in accord to recent experimental results which have shown that the near-cathode voltage drop in high-pressure arc discharges may be that high. It is found that a non-monotony of the dependence of the energy flux density on the surface temperature at fixed values of the near-cathode voltage drop is caused by one of the three mechanisms: overcoming of the increase of combined ion and plasma electron heating by the increase of thermionic cooling as the plasma approaches full ionization; non-monotony of the dependence of the ion current on the electron temperature which is caused by the deviation of the ion current from the diffusion value; rapid increase of the plasma electron heating which is subsequently overcome by thermionic cooling. A closed description of the plasma–cathode interaction is obtained by numerically solving the nonlinear boundary-value problem for the temperature distribution inside the cathode body. Results of numerical modelling of the diffuse discharge under conditions of a model arc lamp are given and a good agreement with the experimental data is shown.